2023
DOI: 10.1021/acs.langmuir.3c00432
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Role of Temperature and Salinity in Aggregation of Nonionic Surfactant-Coated Silica Nanoparticles

Abstract: The adsorption of nonionic surfactants onto hydrophilic nanoparticles (NPs) is anticipated to increase their stability in aqueous medium. While nonionic surfactants show salinity- and temperature-dependent bulk phase behavior in water, the effects of these two solvent parameters on surfactant adsorption and self-assembly onto NPs are poorly understood. In this study, we combine adsorption isotherms, dispersion transmittance, and small-angle neutron scattering (SANS) to investigate the effects of salinity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Here the use of buffer solutions was intentionally avoided as increasing the ionic strength (due to the presence of buffers) will not only alter the interactions of the PFCA with MPs but also influence the hydrophobic interactions between the tails of the PFCA molecules and impact corresponding adsorption behavior. 36 Further work is needed to delineate the roles of pH, ionic strength, and ionization state of the headgroup on the adsorption of PFCAs onto solid–liquid interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the use of buffer solutions was intentionally avoided as increasing the ionic strength (due to the presence of buffers) will not only alter the interactions of the PFCA with MPs but also influence the hydrophobic interactions between the tails of the PFCA molecules and impact corresponding adsorption behavior. 36 Further work is needed to delineate the roles of pH, ionic strength, and ionization state of the headgroup on the adsorption of PFCAs onto solid–liquid interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the model PFCAs in DI water was determined using pendant drop tensiometry performed on an optical tensiometer (Biolin Scientic) and corresponding pendant droplet shape analysis. [33][34][35][36] Optical tensiometry and pendant drop analysis is a traditional method to determine surfactant concentrations in water. Pendant drop analysis involves suspending a drop of the liquid phase from the tip of a needle or capillary tube.…”
Section: Optical Tensiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although parabola-type formulas have been reported in some cases, gemini or cationic surfactants have to be used in these formulas, and the vertex of the parabola is located in the high-temperature region, higher than room temperature. , In the meantime, most of the rheological studies have focused on dilute system solution, and only a few reports have studied the concentrated surfactant solution, which is close to the real applications. It has been reported that, in a concentrated solution, a giant micelle including wormlike micelle will be formed, which is an important hotspot in surfactant studies due to its unique polymer-like behavior. , In dilute surfactant systems, the shape transition of micelles can be studied by static and dynamic light scattering, while it is not feasible in a concentrated solution. Thus, the giant micelle for the latter has been studied by rheology, NMR, SANS, and visually FF-TEM or cryo-TEM. …”
Section: Introductionmentioning
confidence: 99%
“…Ma et al recently observed that the aggregation of silica nanoparticles in the presence of non-ionic surfactants depends on the salinity of the dispersing medium and temperature. 53 Physical adsorption is also related to the behavior of nanoparticles in biological systems. For example, Bharti et al observed that the aggregation of silica nanoparticles is affected by the binding of lysozymes and results in a pH-dependence of the size of aggregates and their internal structure.…”
Section: Introductionmentioning
confidence: 99%